2019
DOI: 10.1111/jace.16854
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling hermetic failure of ceramic tubes by digital image correlation and acoustic emission

Abstract: A new, in situ hermeticity testing apparatus has been developed to allow helium leak evaluation of ceramic tubes, including nuclear‐grade SiC/SiC fuel cladding ceramic matrix composites (CMC), during four‐point bending with simultaneous monitoring of local deformation and damage, using stereoscopic digital image correlation (DIC) and acoustic emissions. The capabilities of the experimental apparatus are demonstrated using alumina, borosilicate glass, and 4130 steel tubes with representative cladding dimensions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…Few measurements of tubular bending properties exist in literature, 29,30 so expected values must be derived from both relevant bending literature sources when available and tubular tension test results. Past results for similar tubular SiC/SiC CMCs under identical four‐point bending have been reported by the authors in Bumgardner, CH, Heim, FM, et al 17 There is a slight increase in the reported Young's modulus compared to past results and expected values for similar tubular specimens; this increase may be attributed to a thicker, more consistent outer CVI matrix coating compared to past claddings. Importantly, expected mechanical performance of tubular, bending specimens generally trails that of planar, tensile specimens 24 .…”
Section: Resultssupporting
confidence: 79%
See 4 more Smart Citations
“…Few measurements of tubular bending properties exist in literature, 29,30 so expected values must be derived from both relevant bending literature sources when available and tubular tension test results. Past results for similar tubular SiC/SiC CMCs under identical four‐point bending have been reported by the authors in Bumgardner, CH, Heim, FM, et al 17 There is a slight increase in the reported Young's modulus compared to past results and expected values for similar tubular specimens; this increase may be attributed to a thicker, more consistent outer CVI matrix coating compared to past claddings. Importantly, expected mechanical performance of tubular, bending specimens generally trails that of planar, tensile specimens 24 .…”
Section: Resultssupporting
confidence: 79%
“…The current failure analysis for both tow structures indicates that matrix cracking occurs preferentially along tow‐to‐tow contact points. For SiC/SiC CMC nuclear fuel cladding tubes which operate with internally pressurized helium gas, delays in significant matrix or coating cracking are desirable to increase the stress at which hermetic seal is lost due to through thickness cracks, which has been found to occur well before fracture of the tow structure 17 . Here, it is seen that in four‐point bending cracks appear to be spaced accordingly to the biased tow spacing; therefore, we can make a few recommendations to CMC manufacturers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations